Quantifying fish behaviour and commercial catch rates in relation to a marine seismic survey. (September 2018) - Bruce, Barry; Bradford, Russ; Foster, Scott; Lee, Kate; Lansdell, Matt; Cooper, Scott; Przeslawski, Rachel
Abstract: The impact of seismic surveys on the catchability of marine fish is a contentious issue, with some claims that seismic surveys may negatively affect catch rates. However little empirical evidence exists to quantify the impacts or identify the mechanisms of such impact. In this study, we used a 2-D seismic survey in the Gippsland Basin, Bass Strait, Australia in April 2015 as an opportunity to quantify fish behaviour (field-based) and commercial fisheries catch (desktop study) across the region before and after airgun operations. Three species found in abundance (gummy shark, swell shark, tiger flathead) were acoustically tagged and released within one of two acoustic arrays (experimental and control zone) and monitored before, during and after the seismic survey. In the field study, only 35% of the gummy sharks and 30% of the swell sharks were subsequently detected two days after release, suggesting movement outside the study area. Various tagged individuals returned sporadically over the monitoring period, including during the seismic survey operations. Behaviour consistent with a possible response to the seismic survey operations was observed for flathead which increased their swimming speed during the seismic survey period and changed their diel movement patterns after the survey. We also investigated the potential impacts of the seismic survey on catch rates using Commonwealth fisheries logbook data from Jan 2012–Oct 2015. Fifteen species and two gear types (Danish seine, gillnet) were modelled to examine differences in catch rates before and after the seismic survey. The catch rates in the six months following the seismic survey were significantly different than predicted in nine out of the 15 species examined, with six species (tiger flathead, goatfish, elephantfish, boarfish, broadnose shark and school shark) showing increases in catch following the seismic survey, and three species (gummy shark, red gurnard, and sawshark) showing reductions. With the exception of flathead movement, we found little evidence for consistent behavioural or catch rate changes induced by the seismic survey in the targeted species, although behavioural data were limited because many sharks left the acoustic receiver array prior to the commencement of the seismic survey. Highlights: We compared acoustic telemetry and fisheries data to a 2015 seismic survey in the Bass Strait. Many sharks left the area soon after release, but several returned during seismic operations. Tiger flathead increased swimming speed during the seismic survey period. Commercial catch rates following the seismic survey were higher in 6 species and lower in 3 species. There was little evidence of consistent behavioural or catch rate change due to the seismic survey.